Psychological and functional problems of children and adolescents with cerebral palsy from the neurodevelopmental perspective - Rok-Bujko, Paulina; Kawecka, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2023)
The main aim of this article was to review some psychological and psychiatric problems in children and adolescents with cerebral palsy (CP) in the context of individual development. The problems in gaining the appropriate experiences during sensitive periods of development were also considered. The risk factors were described and it was revealed that physical activity, sleep problems and pain accounted for the incidence of depression and other mental health problems in patients with CP. Reviewed studies showed that children with CP are at greater risk of having other neurodevelopment disorders, which means that they should be carefully diagnosed for a wider range of problems. The need of expected experiences and proper stimulations, obligatory for brain and mental development during sensitive periods, should also be taken into consideration as CP may restrict or limit the opportunity to receive them.